Runaway wives, urban crimes, and survival tactics in wartime Beijing, 1937-1949 - Ma, Zhao, 1973- (Harvard East Asian monographs, 2015)
"Explores intimate accounts of lower-class women's struggles with poverty, deprivation, and marital strife in wartime Beijing between 1936 and 1945, revealing an urban underworld built on an informal economy and conducted primarily through neighborhood networks"--